DESIGN & EVALUATION OF PULSATILE DRUG DELIVERY SYSTEM OF ATENOLOL FOR CHRONOMODULATED THERAPY - AMOL M (International Journal of Pharma and Bio Sciences, 2012)
The present work deals with the study and development of an oral dosage form devised to release drug following a programmed time period after administration. Pulsatile release tablet comprises of a drug containing core and pH sensitive polymeric coating capable of delaying drug release and providing gastric resistance to overcome gastric emptying variability, thus allowing colon delivery to be pursued according to the time dependent approach. The aim of this work is to evaluate different pH sensitive polymers ( Eudragit S 100, ethyl Cellulose, sodium alginate) at different ratio in developing a suitable dosage form, exhibiting a no drug release in upper regions of gastrointestinal tract (GIT) in order to provide site specificity as well as time controlled formulation.Prepared tablets are characterized for physical parameters, drug content drug release, lag time, stability studies.